비안와두부형 뮤코르진균증의 임상양상 3예 - 송유미; Yoo Mi Song; 강일봉; Il Bong Kang; 신선영; Sun Young Shin (Daihan angwa haghoi jabji, 2007)
목적 : 비안와두부형 뮤코르진균증의 눈의 증상을 포함한 다양한 임상양상을 경험하였기에 문헌 고찰과 함께 보고하고자 한다. 대상과 방법 : 조절되지 않는 당뇨를 가진 환자에서 비안와두부형 뮤코르진균증이 발생한 3가지 증례를 경험하였다. 결과 : 본 증례들에서 안검하수, 안근마비, 시력 및 시야장애, 안구통 등의 다양한 안과적 증상을 나타냈고 내원 2일이내에 항진균제 치료를 시작하였으나 모두 사망에 이르렀다. 결론 : 비안와두부형 뮤코르진균증은 여러가지 안과적 증상을 나타낼 수 있어 임상적으로 주목할 만하다. <한안지 48(4):593-598, 2007> Purpose: To report upon several cases of rhino-orbito-cerebral mucormycosis with variable clinical manifestations including ocular symptoms. Methods: We documented three patients with rhino-orbital-cerebral mucormycosis and uncontrolled diabetes. Results: The patients presented variable ophthalmic symptoms including blepharoptosis, ophthalmoplegia, visual disturbance, visual field defect and ocular pain. Despite administration of an antifungal agent within two days, all of the patients died. Conclusions: We reported the cases of three patients with rhino-orbito-cerebral mucormycosis presenting ophthalmic symptoms with a literature review. Variable initial symptoms were emphasized in making diagnosis of rhino-orbito-cerebral mucormycosis. J Korean Ophthalmol Soc 48(4):593-598, 2007